2011
DOI: 10.1029/2009jb007060
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of branching models for seismicity and likelihood maximization through simulated annealing

Abstract: [1] Stochastic branching models provide a good description of some aspects of the temporal organization in seismicity. Generally, they assume that magnitudes are independent of history, as in the widely used Epidemic Type Aftershock Sequence (ETAS) model. Here, we consider a recent epidemic-like model where time-magnitude and magnitude-magnitude correlations are introduced via a dynamical scaling (DS) hypothesis, namely, the magnitude difference between earthquakes fixes the time scale for correlations. We als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…In our study we take explicitly into account the aftershock incompleteness adopting the same procedure developed in [ 40 ] to reproduce both the non-trivial dependence of the c -value in the OU law on the mainshock magnitude [ 8 , 41 , 42 , 43 , 44 , 45 , 46 ], as well as the non trivial magnitude correlations between subsequent earthquakes [ 11 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The model, defined as ETASI2 model, implements aftershock incompleteness by multiplying the occurrence rate in Equation ( 1 ) by a detection rate function of the magnitude represented by the cumulative distribution function of the normal distribution.…”
Section: Epidemic Models For Aftershocks and Foreshock Occurrencementioning
confidence: 99%
“…In our study we take explicitly into account the aftershock incompleteness adopting the same procedure developed in [ 40 ] to reproduce both the non-trivial dependence of the c -value in the OU law on the mainshock magnitude [ 8 , 41 , 42 , 43 , 44 , 45 , 46 ], as well as the non trivial magnitude correlations between subsequent earthquakes [ 11 , 47 , 48 , 49 , 50 , 51 , 52 , 53 ]. The model, defined as ETASI2 model, implements aftershock incompleteness by multiplying the occurrence rate in Equation ( 1 ) by a detection rate function of the magnitude represented by the cumulative distribution function of the normal distribution.…”
Section: Epidemic Models For Aftershocks and Foreshock Occurrencementioning
confidence: 99%
“…We attribute these deviations to the cascading process that can produce a more gradual decrease of the aftershock number from the initial plateau compared to the situation when higher‐order generation aftershocks are not taken into account (Hainzl, ). A better fit for F ( x ) in numerical and instrumental catalogs is provided by Ffalse(xfalse)=Alog()1+Bxp obtained by Lippiello, Bottiglieri, et al () under a dynamical scaling assumption (Bottiglieri et al, , , ; de Arcangelis et al, ; Lippiello, Godano, & de Arcangelis, ; Lippiello et al, , ). This choice of F ( x ) reduces the value of the χ ‐squared by a factor 5 with respect to the OU law, even if the agreement with experimental data is still very poor according to a Pearson's χ ‐squared test.…”
Section: The Overlap Of Seismic Waveforms and Data Incompletenessmentioning
confidence: 99%
“…obtained by Lippiello, Bottiglieri, et al (2007) under a dynamical scaling assumption (Bottiglieri et al, 2009(Bottiglieri et al, , 2010(Bottiglieri et al, , 2011de Arcangelis et al, 2016;Lippiello et al, 2009Lippiello et al, , 2013. This choice of F(x) reduces the value of the -squared by a factor 5 with respect to the OU law, even if the agreement with experimental data is still very poor according to a Pearson's -squared test.…”
Section: The Etasi Modelmentioning
confidence: 99%
“…We attribute these deviations to the cascading process which can produce a more gradual decrease of the aftershock number from the initial plateau compared to the situation when higher order generation aftershocks are not taken into account [12]. A better fit for F(x) in numerical and instrumental catalogs is provided by F(x) = A log (1 + Bx −p ) obtained by Lippiello et al [46] under a dynamical scaling assumption [38,45,[47][48][49][50][51].…”
Section: The Etasi Modelmentioning
confidence: 95%
“…Deviations from the GR law are a natural consequence of this assumption with a completeness magnitude depending on time in agreement with what is observed in experimental data (Equation (2)). The study of the maximum likelihood [51] has shown that this method provides a more accurate description of the aftershock rate decay than the ETAS model.…”
Section: Dynamical Scaling Etas Modelmentioning
confidence: 99%